The Malleable Brand: The Role of Implicit Theories in Evaluating Brand Extensions - Yorkston, Eric A.; Nunes, Joseph C.; Matta, Shashi (Journal of Marketing, 2010)
This research documents how implicit theories regarding personality traits (whether they are deemed to be fixed or malleable) affect consumer inferences about the malleability of a brand's personality traits and, thus, its ability to extend into new categories. Study 1 documents that consumers who believe that traits are malleable (incremental theorists) are more accepting of brand extensions than consumers who believe that traits are fixed (entity theorists). These results hold whether implicit theories are measured or manipulated. Study 2 reveals how implicit theories affect consumers’ perceptions regarding the flexibility of a brand's personality traits and not its physical traits. Study 3 demonstrates that consumers primed with different implicit theory orientations respond differently to varying degrees of change within a single trait. This study tests the limits of the effect and demonstrates the impact of using primes embedded within standard marketing communication.